2017
DOI: 10.1136/jim-2016-000193
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Soluble α-Klotho Levels in Patients with Autosomal Dominant Polycystic Kidney Disease

Abstract: This study aims to determine fibroblast growth factor-23 and soluble α-Klotho levels in patients with autosomal dominant polycystic kidney disease. A total of 76 patients with autosomal dominant polycystic kidney disease and 32 healthy volunteers were included in the study. Serum fibroblast growth factor-23 and soluble α-Klotho levels were measured with ELISA kits. Parathyroid hormone, phosphate, calcium, creatinine, 25-hydroxyvitamin D3 levels, urinary protein to creatinine ratio and estimated glomerular filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
(68 reference statements)
3
7
0
Order By: Relevance
“…We further found out that in the Hp 2-2 genotype, α -klotho renal expression is gradually reduced with the progression in CKD stages, and this decrease is more prominent in the diabetic state. This association is in agreement with previous studies that have shown that renal α-klotho gene expression is regulated by pathophysiological conditions including hypertension, diabetes, and chronic renal failure in animal models and in humans [ 16 , 17 , 20 , 29 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We further found out that in the Hp 2-2 genotype, α -klotho renal expression is gradually reduced with the progression in CKD stages, and this decrease is more prominent in the diabetic state. This association is in agreement with previous studies that have shown that renal α-klotho gene expression is regulated by pathophysiological conditions including hypertension, diabetes, and chronic renal failure in animal models and in humans [ 16 , 17 , 20 , 29 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have indicated that renal α-klotho gene expression is regulated by pathophysiological conditions including long-term hypertension, oxidative stress, diabetes, and chronic renal failure in both animal models and humans [ 16 , 17 , 20 , 29 32 ]. Hence, we evaluated whether the increased renal iron deposits associated with the Hp 2-2 genotype also affect the α -klotho renal expression both in DN mice and patients.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the research states that the eGFR decrease is correlated with FGF-23 concentration increase in ADPKD and CKD patients in both adults [13][14][15][16] and children [8,[17][18][19][20][21]. The highest concentration of FGF-23 was found among patients with end-stage renal disease [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…Klotho protein concentration increased as the eGFR increased, which was observed in the total cohort group. Information about Klotho protein fluctuations during CKD progression are disparate [13][14][15][16][17][18][19][26][27][28][29]. Most of the available research says that adult patients with ADPKD experience serum Klotho concentration decrease with the progression of CKD [13-15, 26, 27]; the same can also be observed in children [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation